Blockchains Technology Analysis: Applications, Current Trends and Future DirectionsâAn Overview - Junejo, A.Z. (Springer, 2020)
One of the most promising technical trends that have taken the world by storm is the blockchain technology which is the underlying mechanism of the bitcoin. It is a distributed, decentralized and innovative technology that is predicted to bring a huge change in the world. This technology is analogous to the Internet with built-in robustness. Although it is currently one of the most researched areas in the domain of information technology, it has a set of its own limitations. This paper discusses the blockchain technology from scratch, starting off with the general introduction followed by presentation of a comprehensive insight into blockchain applications, the current research trends, limitations and potential future directions. The paper concludes that blockchain networks are likely to change the outlook, perspectives and utilization techniques of the information technology industry in the future by decentralizing the World Wide Web and making the traditional business defunct. Moreover, the amalgamation of blockchain technology with IoT and data science is going to open new horizons of research and development in tech world. Â© Springer Nature Singapore Pte Ltd. 2020.